Approaches to the management of ovarian cysts in pregnancy: A case series (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The incidence of ovarian cysts in pregnancy is postulated to be approximately 3%. Most ofthese cysts are benign, with 6% of them being benign. Most of these masses are diagnosed incidentallyduring routine ultrasound. The most common are functional cysts. Most of these cysts do not havesymptoms and are managed conservatively. For persistent symptomatic cysts, medical and surgicalmanagement is a viable option.Case series: We present cases of three patients, two of whom were managed conservatively. One of thepatients with a corpus luteum cyst was managed surgically and did well, whereas the other two patientswere noted to have asymptomatic dermoid cysts. Pregnancy outcomes for the two who delivered wereunaffected, including their modes of delivery.Conclusion: Adnexal masses are common during pregnancy. There is a need to evaluate andcharacterize these masses even during pregnancy. Management options for adnexal masses areprimarily conservative, but for masses that meet the criteria for surgical management, surgery is safe,especially in the second trimester. A laparoscopic approach for abdominal surgery in the second trimesteris feasible and relatively safe, as demonstrated in the present case. Modification of entry and surgicalapproaches and preoperative planning are important when considering surgery during pregnancy. Reliefof pain symptoms during pregnancy will lead to a positive pregnancy experience.